Status of supplementary feeding of reindeer in Sweden and its consequences - Persson, Anna-Marja (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Reindeer husbandry in Sweden is suffering from great challenges, where fragmentation of the landscape and climate change are affecting winter grazing grounds. Lichen availability is seen as the bottleneck for further existence of this livelihood, but supplementary feeding has been used to different extents to compensate for the loss of lichen pastures. The status and the level of supplementary feeding of reindeer in Sweden is little documented. I conducted a questionnaire survey addressed to all the 51 reindeer herding districts in Sweden with the objectives to document the level of feeding, the practices being used during feeding and the experiences from feeding. Based on answers from 160 herders in 40 districts, I found that feeding was frequently practiced in almost all herding districts, although to different extent and for different reasons. Herders reported benefits of feeding such as better condition and higher survival for example; and problems with feeding such as feed related diseases, infectious outbreaks, and economic challenges due to expenses for feed and negative behavioral changes of the reindeer. Statistical analyses revealed that both calving success and reindeer body condition in autumn (based on carcass weights of slaughtered calves) could be correlated with the extent of feeding. For herders that had fed regularly during several years I found that calf carcass weight had increased over the time. The proportion of the costs, the extra work load and the long-term negative effects related to feeding need to be considered in relation to the possible benefits from feeding.